Functional development of mechanosensitive hair cells in stem cell-derived organoids parallels native vestibular hair cells - Xiao-Ping Liu (Nature Portfolio, 2016)
Sensory hair cells from the mammalian inner ear do not regenerate. Here, the authors induce direct hair cell formation from mouse embryonic stem cells using a three-dimensional culture system and observe differentiation of Type I and Type II vestibular hair cells and establishment of synapses with neurons.